Green Hotel Implementation in Indonesia: A Focus on Java and Bali - Alkotdriyah, Putri Puspa (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2024)
Purpose: This study explores the importance of green hotels in Indonesia and highlights their role in protecting the environment and mitigating climate change. It also explores the consumer market for environmentally friendly products and the demands of private businesses to adopt green management to reduce environmental impact and improve user experience. Despite challenges such as strict restrictions, this study aimed to understand the use of green hotels in Java and Bali, focusing on the government's role in management. Design/Methodology/Approach: This review is based on research literature on green hotels in Indonesia, which includes academic literature, research publications, journals, government regulations, and online sources. Research Findings: Research shows that although Java and Bali are leaders in the use of green hotels, there is still room for improvement in their practices. Research limitations/conclusions: This study was used only to analyze the usage of green hotels in Java and Bali because these hotels have higher rates compared to other parts of Indonesia. Implications: The findings provide insights for stakeholders, including hotel management and government, to improve green hotel practices and policies. Originality/value: This study contributes to the existing literature by providing a comprehensive evaluation of green hotel practices in Indonesia, presenting the views of various stakeholders who influence and highlight the importance of leadership in the hotel industry.